2022
DOI: 10.1128/jvi.01949-21
|View full text |Cite
|
Sign up to set email alerts
|

Short-Stalk Isoforms of CADM1 and CADM2 Trigger Neuropathogenic Measles Virus-Mediated Membrane Fusion by Interacting with the Viral Hemagglutinin

Abstract: Measles virus (MeV), an enveloped RNA virus in the family Paramyxoviridae , usually causes acute febrile illness with skin rash, but in rare cases persists in the brain, causing a progressive neurological disorder, subacute sclerosing panencephalitis (SSPE). MeV bears two envelope glycoproteins, the hemagglutinin (H) and fusion (F) proteins. The H protein possesses a head domain that initially mediates receptor binding and a stalk domain that subsequently transmits the fusion-triggering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Following procedures previously described in ( 14 ), 293FT cells cultured on 12-well plates were transfected with 0.5 μg of pCA7 encoding one of FLAG-tagged F proteins with 0.5 μg of pCA7 encoding E-cadherin (a cell surface protein control) using Lipofectamine LTX. At 24 hours after transfection, cells were washed with phosphate-buffered saline (PBS) and then incubated with 200 μl of the biotin reagent solution [2 mM EZ-Link N -hydroxysulfosuccinimide (sulfo-NHS)–biotin (Thermo Fisher Scientific) in PBS] for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following procedures previously described in ( 14 ), 293FT cells cultured on 12-well plates were transfected with 0.5 μg of pCA7 encoding one of FLAG-tagged F proteins with 0.5 μg of pCA7 encoding E-cadherin (a cell surface protein control) using Lipofectamine LTX. At 24 hours after transfection, cells were washed with phosphate-buffered saline (PBS) and then incubated with 200 μl of the biotin reagent solution [2 mM EZ-Link N -hydroxysulfosuccinimide (sulfo-NHS)–biotin (Thermo Fisher Scientific) in PBS] for 30 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Following procedures previously described in ( 14 ), proteins in samples were separated by SDS–polyacrylamide gel electrophoresis and then blotted onto polyvinylidene difluoride membranes (Hybond-P, Amersham Biosciences). The membranes were incubated with primary antibodies (Abs) for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MeV infection, there is a late complication called subacute sclerosing encephalitis (SSPE) that arises from persistent infection in the brain, and viruses isolated from patients with SSPE have mutant fusion (F) proteins with high fusion ability. These mutant F proteins with high cell fusion ability are expressed on the same cells as cell adhesion molecule (CADM) 1 and 2 (called “cis” interactions), leading to cell fusion through the binding actions of these molecules 122,123 . Because these mutant F proteins differ in ability from the field strains, 124 it remains unclear whether natural morbillivirus infection in the CNS utilizes a similar mechanism.…”
Section: Pathology Of Morbillivirusesmentioning
confidence: 99%
“…These mutant F proteins with high cell fusion ability are expressed on the same cells as cell adhesion molecule (CADM) 1 and 2 (called "cis" interactions), leading to cell fusion through the binding actions of these molecules. 122,123 Because these mutant F proteins differ in ability from the field strains, 124 it remains unclear whether natural morbillivirus infection in the CNS utilizes a similar mechanism. However, experiments using F proteins isolated from patients with measles inclusion body encephalitis (F proteins containing a mutation for high cell fusion capacity) showed that MeV strains with these mutated F proteins caused CNS invasion through the respiratory route, 125 suggesting that the cell fusion capacity of the F protein is related to its neuropathogenic potential.…”
Section: Pathology Of the Six Species Of Morbilliviruses Except Femvmentioning
confidence: 99%